RESERVATION GOODS SYSTEM IN PD. RAFISI PERDANA USING VISUAL BASIC 6.0 - ENDANG RIYANTI (Jurnal Sistem Informasi, 2007)
In the era of rapid globalization and computerization of current developments, there are still companies that still use manual systems in preparing reports - reports that the company needed a time-consuming. System sales for companies that are not computerized can often cause delays & not the accuracy of the data or information generated. Hence the need to use computers as tools in pengelolahan data, so the data or information is received more quickly, precise, and accurate in a company.